National Markets and New Defenses: The Case for an East Asian Opt-in Takeover Law - Pak, Bliss Burdett (Columbia Journal of Asian Law, 2007)
The arrival of Anglo-Saxon source capital to East Asia has brought with it the debate over corporate takeover defenses and the appropriate allocation of power among shareholders and directors of public companies. Takeover defenses such as poison pills, staggered boards and judicial permission to “just say no” to an unsolicited takeover bid all are the focus of intense discussion among companies that, due to prior state or family control, had previously been immune to takeover attempts. Complicating the debate is the history of cross- and circular- shareholdings, which has worked in East Asia to concentrate control of a vast proportion of national resources in a few corporate conglomerates. Additionally complicating and coloring the policy debate is the impact of foreign investors in national champion companies, and the often- divergent interests and expectations among financial investors, shareholder activists, local employees and other stakeholders.